Goenawan Mohamad Berpikir tentang Puisi dan Berpuisi dengan Ironi - Abdul Rozak Zaidan (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
Goenawan Mohamad thought about poetry and from that we know his thought about the essence of poetry. And then, Goenawan wrote his poetry with irony and we find out that irony is a means of communication in his poetry. The twothings will be discussed in this  simple paper chronologically as an effort to understand further the poetries ofGoenawan Mohamad compiled in two anthologies of the 1970s, Pariksit and Interlude: Pada Sebuah Pantai.